Integration Of The Right To Inclusive And Equitable Education In Higher Education - Asriati Asriati; Imran Eka Saputra; Salle Salle (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Based on the provisions of articles 28A to 28J of the 1945 Constitution, the state is obliged to fulfill, protect and respect the human rights of every citizen. This guarantee is not just written without reason or purpose, but this guarantee must protect every human being from the use of unlimited power or the actions of authorities who act arbitrarily. The research method uses library research, namely a research process carried out through collecting data and information from various related sources. The results of the research in this paper are that the right to education must be accessible to anyone regardless of the individual's background, so that everyone can receive education equally. Fulfillment of this right is implemented in the form of providing facilities, access or resources that enable the fulfillment of the right to education to all people, both those who have the ability to finance their education and those who do not have the ability to finance their education, or based on differences in ethnicity, religion, race, class. , gender, different social backgrounds